Evaluación del impacto de políticas públicas del PNBV en organizaciones agro-productivas solidarias de los Cantones El Carmen y Pedernales. - Peralta Zambrano, Zindy Paola (2018)
The objective of the research was to evaluate the impact of the public policies of the Good Living National Plan 2013 - 2017, focused on the agro-productive solidarity organizations of the Carmen and Pedernales cantons. Methodologies were applied to achieve this objective. The discourse analysis that allowed to conceive the basis of the theoretical political argument, also used research tools, such as a questionnaire based on the Living Conditions Survey conducted by the INEC. We proceeded to make a diagnosis of the associations, for the calculation of the stratified sample of the associations and a control sample based on the branch of activity of the INEC. Once all the information was collected from both the associated and non-associated persons, the statistical software IBM SPSS was used to enter and process all the data by means of tables. In addition, a matrix was developed to link the questions with each strategic guideline, in order to facilitate the analysis of compliance with the policies, taking 6 of 12 objectives evaluated. Evidencing with a generalized table the effective compliance, partial compliance and non-compliance of the policies, according to the information collected in the agro-productive organizations.